2020
DOI: 10.1111/ajps.12519
|View full text |Cite
|
Sign up to set email alerts
|

If They Endorse It, I Can't Trust It: How Outgroup Leader Endorsements Undercut Public Support for Civil War Peace Settlements

Abstract: Civil wars are a greater source of violence than any other type of conflict, yet little is known about one of the key determinants of civil war peace settlement success: civilian support. We evaluate how a core component of nearly all peace settlements, leader endorsements, affects public support. We predict that individuals in conflict settings will view settlements endorsed by outgroup leaders as less trustworthy and that they will become less supportive. We conduct an endorsement experiment with nearly 1,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…We similarly expect that COVID-19 policies from bipartisan coalitions of liberal and conservative elites will be supported more than policies from only liberal or conservative politicians. Ordinary people value political cooperation ( 41 , 42 ) and are responsive to whether proposals are backed by trusted political elites ( 43 , 44 ). Previous research suggests that people are more swayed by the stances of their fellow ingroup than outgroup members ( 22 , 23 ), making it unlikely that the mere presence of outgroup politicians will completely dampen support for bipartisan policies.…”
Section: Depolarizing Experts and Bipartisan Coalitionsmentioning
confidence: 99%
“…We similarly expect that COVID-19 policies from bipartisan coalitions of liberal and conservative elites will be supported more than policies from only liberal or conservative politicians. Ordinary people value political cooperation ( 41 , 42 ) and are responsive to whether proposals are backed by trusted political elites ( 43 , 44 ). Previous research suggests that people are more swayed by the stances of their fellow ingroup than outgroup members ( 22 , 23 ), making it unlikely that the mere presence of outgroup politicians will completely dampen support for bipartisan policies.…”
Section: Depolarizing Experts and Bipartisan Coalitionsmentioning
confidence: 99%
“…Three distinct strands of inquiry have emerged from this literature, each with its associated strengths and limitations. First, a number of studies explicitly examine citizen attitudes towards ongoing peace processes and the support citizens are willing to lend in order to make peace settlements a reality (Fabbe, Hazlett, and Sınmazdemir 2019; Haas and Khadka 2020; Tellez 2019b). Thus far, most of these studies focus only on the immediate aftermath of fighting.…”
Section: Literaturementioning
confidence: 99%
“…In addition, electoral competition facilitates political parties to put forth platforms and messages in favour of or against the different provisions included in a peace agreement that resonate with voters’ concerns. Recent research has demonstrated that citizens’ attitudes towards different components of the peace agreements signed in Colombia and South Sudan are driven by cues from polarising elites (Garbiras-Díaz et al, 2019; Haas and Khadka, 2020).…”
Section: How War and Political Experiences Shape Citizens’ Attitudes mentioning
confidence: 99%